Identifikasi Senyawa Antijamur Colletotrichum orbiculare dari Filtrat Azotobacter sp. - HUTAGAOL, FRELIANT ENES GALETY; KHALIMI, KHAMDAN; SUPUTRA, I PUTU WIRYA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.12, No.1, Januari 2023, 2023)
Identification of the Colletotrichum orbiculare antifungal compound from the filtrate of Azotobacter sp. The Anthracnose of watermelon plants caused by the fungus Colletotrichum orbiculare. These pathogens generally live on infected plant residues or on alternative hosts. Utilization of Azotobacter bacteria as a biocontrol against fungal pathogens that cause anthracnose disease in melon plants. The purpose of this study was to determine the antifungal activity of Azotobacter sp. against the fungus C. orbiculare in vitro and to identify antifungal compounds in Azotobacter sp. Filtrate. The results showed that Azotobacter sp. was able to inhibit the growth of the fungus C. orbiculare with a percentage of inhibition of 86.81%, when compared to the control in in vitro testing. Azotobacter sp. Filtrate at a concentration of 50% was able to inhibit the growth of the fungus C. orbiculare with a percentage of inhibitory power of (98.99%) when compared to the control in in vitro testing. The results of GCMS analysis showed that the antifungal compounds produced by Azotobacter sp. Pp3 are 2,4 Dichlorobenzaldehyde; 3,3-dimethylbutylbis (trifluoromethyl)boranemethylglycine;1,2-Diethyl-5-undecylpyrolidine;1-(3,4-dichlorophenyl) cyclopropane carboxylic acid; Acetamide, N-(3,4,5-tribromophenyl)-2-chloro-; 2,3-dihydro-3,5-dihydroxy-6-methyl-4h-pyran-4-one; 2,4,5-Triselena-1,3-diborole,1,3-bis(2,3-dimethylbut-2-yl)-; Pentanal,5-hydroxy-,(2,4-dinitrophenyl)hydrazone;Dithiocarbamate, S-methyl-,N-(2-methyl-3-oxobutyl)-;1-Chloro-2-methyl-1-morpholino-1,3-butadiene;Silane, [[3-(3-bromophenyl)-3-butenyl]oxy]trimethyl-;Acetimide,2,2,2-trifluoro-n-hexyl. The results of this study provide new information about antifungal compounds that have antifungal activity against the fungus C. orbiculare .